Multi-key Modified Tiny Encryption Algorithm for HealthCare - Aradhyamath, Sharath; Paulose, Joy (International Journal of Engineering and Technology, 2018)
Healthcare data is crucial in patient’s surveillance. To give the finest treatment to patients the data should be of the best quality. Many security threats affect the integrity and ingenuity of the medical data. In the recent times, medical data can be accessed anytime and anywhere with the help of an overwhelming technology called the Internet of Things (IoT). IoT has numerous applications based on healthcare, however, it facilitates data misuse such as data breach and health care fraud. Sensitive and protected data is stolen and modified by an unauthorized person. Due to these data abuses, it degrades the quality of medical data and service. In this paper, secure data transfer is done in IoT based healthcare to enhance the security of the medical data. Data confidentiality can be achieved using encryption algorithms such as Tiny Encryption Algorithm (TEA) which is lightweight and suitable for resource constraint devices. The results of the proposed system show that the modified TEA overcomes the drawback of the equivalent key and also provides a better security to healthcare data.